2018
DOI: 10.1007/s12094-018-1943-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in radiation oncology: proposal of the Spanish Society of Radiation Oncology (SEOR) for a continuous improvement of the quality of care in oncology

Abstract: Current cancer treatment options include surgical intervention, radiotherapy and chemotherapy. The quality of the provision of each of them and their effective coordination determines the results in terms of benefit/risk.Regarding the radiation oncology treatments, there are not stabilised quality indicators to be used to perform control and continuous improvement processes for healthcare services. Therefore, the Spanish Society of Radiation Oncology has undertaken a comprehensive project to establish quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Perhaps the most recent and relevant ROQI development paper comes from the Spanish Society of Radiation Oncology (SEOR) 23 . They carried out a systematic literature search and 2‐round Delphi process for 28 ROQIs.…”
Section: General Roqismentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps the most recent and relevant ROQI development paper comes from the Spanish Society of Radiation Oncology (SEOR) 23 . They carried out a systematic literature search and 2‐round Delphi process for 28 ROQIs.…”
Section: General Roqismentioning
confidence: 99%
“…Increasing the number of meaningful ROQIs relating to structure also requires collection to be feasible and reproducible. One possible example, as suggested by SEOR is to consider a ROQI relating to RT facility volume for highly complex definitive curative intent RT, like for surgery 23 . A retrospective multivariate analysis from the American national cancer database recently showed that for certain tumour sites treated with definitive RT (Lung and head and neck cancers) this correlated with improved overall survival 39 .…”
Section: Gaps In Roqismentioning
confidence: 99%
See 2 more Smart Citations
“…Quality Research in Radiation Oncology). [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, these measures remain quite limited in defining the quality of care received. 33 This is due to a lack of a clearly defined link between process and outcome, as well as uncertainty regarding the magnitude of effect on functional and oncological outcomes from non-adherence.…”
Section: Radiotherapymentioning
confidence: 99%